2007
DOI: 10.1002/ejic.200601003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Protonation and Interaction with Anions on a Lead(II) Complex with a Lateral Macrobicycle Containing a Phenol Schiff‐Base Spacer

Abstract: The macrobicycle receptor L 4 , derived from 1,10-diaza-15-crown-5 incorporating a phenol Schiff-base spacer, forms stable complexes with lead(II). In [Pb(L 4 )(ClO 4 )](ClO 4 )· CH 3 CN (1), the lead(II) ion is asymmetrically placed at the one end of the macrobicyclic cavity, because of the intramolecular hydrogen bonding interaction that occurs between an imine nitrogen atom and the phenol group. This asymmetric position of the metal ion inside the macrobicyclic cavity induces chirality in this system. Varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
(43 reference statements)
1
13
0
Order By: Relevance
“…We have previously reported that reaction of L 1 and L 2 with dialdehydes leads to the formation of lateral macrobicyclic structures that are useful for the coordination of both cations and anions [27][28][29]. We have found that these macrobicycles cannot be prepared by direct reaction between the organic precursors due to the anti arrangement adopted by the diamines L 1 and L 2 , but Ba(II) can act as an effective template, thereby facilitating the formation of the desired macrobicycles in high yields [30].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that reaction of L 1 and L 2 with dialdehydes leads to the formation of lateral macrobicyclic structures that are useful for the coordination of both cations and anions [27][28][29]. We have found that these macrobicycles cannot be prepared by direct reaction between the organic precursors due to the anti arrangement adopted by the diamines L 1 and L 2 , but Ba(II) can act as an effective template, thereby facilitating the formation of the desired macrobicycles in high yields [30].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20] Relying on the intermediate character of lead(II) in Pearson's HSAB classification, [21][22][23] mixed ligands that combine soft (e.g., sulfur) or intermediate bases (e.g., neutral carbonyl oxygen atoms) with a harder base like an amino nitrogen atom appear to be particularly adapted to sequester Pb 2+ . [21,[24][25][26] This rationale is found behind all currently approved drugs used in chelation therapy for treating chronic lead overloads. [27][28][29][30][31] From a stereochemical point of view, the Pb 2+ ion possesses an electronic lone pair (6s 2 ) that can be either stereochemically active, as a consequence of the hybridization of the 6s 2 with the unoccupied 6p 0 orbitals, or inactive according to the Valence Shell Electron Pair Repulsion (VSEPR) formalism.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic behavior observed in acetonitrile solution can be attributed to a translocation of the Zn II ion from one end of the macrocyclic cavity to the second one, as it was previously observed for a Pb II complex with a macrobicyclic ligand containing a 1,10-diaza-15-crown-5 moiety. [27] If it is assumed that the exchange process associated with this line broadening (before coalescence) is slow on the NMR timescale, then (6), or Cu (7) in good yield (42-63 %). The IR spectra (KBr disks) show a band at ca.…”
mentioning
confidence: 99%